Tren Penelitian Voice Behavior Employee Lima Tahun Terakhir: Analisis Bibliometrik dan Studi Naratif - Amaliyah, Khurun In; Puspoyudo, Azzahra Jasmine; Tinduku, Beatrix; Prihatsanti, Unika (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
A situation that is needed in an organization is a situation where employees provide opinions and ideas that support the progress of an organization which is commonly referred to as employee voice behavior. The purpose of this study is to find out 1) the trend of employee voice behavior research, 2) to map studies related to employee voice behavior, 3) to map which countries often conduct research on employee voice behavior, and 4) to explain studies on employee voice behavior. This study uses bibliometric analysis and narrative reviews. The results found in the last five years totaled 413 consisting of book articles, reviews, book chapters, and conference papers on employee voice behavior narrative studies discussing the relationship between employee voice behavior and employee motivation, morality of leadership style, employee performance, paternalistic leadership style and leader-member exchange relationships.  The limitation of this research is that it uses SCOPUS data from the last five years, but 2024 is only entering its second year, so the publications are limited. Researchers suggest further research to use a more diverse database so that the data obtained is more comprehensive.